(untitled) (International Journal of Food and Nutritional Sciences, 2022)
According to the International Monetary Fund, the Indian economy is a "bright spot" in the global context and has the seventh largest nominal GDP and the third largest in terms of purchasing power parity (PPP), and consequently, short-term growth prospects are also positive. Furthermore, India’s GDP grew by 7.6% in 2015–2016, surpassing the World Bank’s growth forecast for the first time (growth expected for 2023–2024 is 7.5 plus). "They know where government policy is on taxation and revenue growth as a budget." It has a direct impact on the economic accessibility of citizens. The use of government revenue collection (usually taxes) and spending (deficits) to influence the economy is known as monetary policy in economics and politics. The stated requirements of economic activity are affected when the government changes tax and spending levels. Monetary policy will be used to stabilise the economy in unstable times. The basic principles of budgeting are taxation, expenditure, investment and withdrawal strategies, and control of debt and surplus. Economic policy is most important in developing countries. The state has a great responsibility to participate in revenue and expenditure in a fair manner. Secondary sources of literature have been consulted for the research. This study attempts to provide strategies for increasing revenue, reducing government expenditure, and reducing taxes to stimulate the economy.